The Effect of Reading Leaflets During the Observation Period After Vaccination on Knowledge of COVID-19 and Vaccines Among Chinese Small Town Residents: A Randomized Controlled Trial - Yu, Si-Yi; Luo, Jun-Jun; Shan, Ke-Shu; Xu, Lei; Ding, Ling; Chen, Xue-Qin (Frontiers in Public Health, 2022)
Background Public health education is essential for epidemic prevention and control in the post-COVID-19 era. This randomized controlled trial (RCT) aims to evaluate the effect of reading leaflets during the observation period after vaccination on knowledge of COVID-19 disease and vaccines in Chinese small town residents and to provide suggestions for public health education. Methods Residents were recruited during the observation period after getting vaccinated against COVID-19 in Xidian and were randomly divided into an education group and a control group. The education group was asked to complete the questionnaire after reading a leaflet, whereas the control group directly completed the questionnaire. The questionnaire comprised two sections on COVID-19 knowledge and vaccine knowledge, and the scores were used to assess the resident's knowledge. Results A total of 142 participants in the education group and 154 participants in the control group were enrolled. The rates of correct knowledge in the education group and the control group were 90.7 and 83.1%, respectively. The scores of the two sections and the aggregate knowledge score of the education group were significantly higher than those of the control group (P < 0.001). The rates of correct responses to questions on clinical manifestations and transmission routes of COVID-19 and indications and contraindications of vaccines significantly increased after reading the leaflets (P < 0.05). Knowledge of different groups of genders, ages, marital statuses, education levels and occupations all improved (P < 0.05), and the 18–29-year-old and never-married group revealed a higher growth rate of correct responses. Conclusion Chinese small town residents have a median level of knowledge regarding COVID-19 disease and vaccines. Reading leaflets during the observation period after vaccination effectively improved their knowledge. This low-cost and efficient health education approach can be widely applied.